ARTISTIC EXPRESSIVENESS OF SOUND DESIGN IN UZBEK ANIMATION - Omonova Parvina Sayfiddin qizi (Modern American Journals, 2025)
The article explores the artistic expressiveness of sound design in Uzbek animation, focusing on how auditory elements shape emotional perception, narrative dynamics, and cultural identity within animated works. Sound design in animation serves not only as a technical process but also as a creative art form that transforms visual narratives into multisensory experiences. The study analyzes the evolution of sound aesthetics in national animation, from early experimental films to contemporary digital productions, emphasizing the synthesis of traditional Uzbek musical motifs, environmental soundscapes, and modern digital effects. Through the analysis of selected examples from the works of Uzbekfilm and independent animation studios, the research identifies the methods of achieving expressive harmony between sound and visual imagery. The paper argues that the integration of acoustic symbolism and narrative rhythm in sound design reinforces the viewer’s emotional connection and enhances the distinct artistic language of Uzbek animation. The results highlight how the collaboration between composers, sound engineers, and animators fosters the development of a unique national sound identity while aligning with global audiovisual trends.
Keywords: Sound design, Uzbek animation, artistic expressiveness, audiovisual synthesis, cultural identity, musical motifs, soundscape, emotional impact, digital production, narrative rhythm